Will Trent : Criminal - Book 6 - Slaughter, Karin; 1971- (Dell Books, 2016)
A Georgia Bureau of Investigation search into a shocking crime from 1975 poses unprecedented personal and professional challenges for top agent Will Trent, who encounters threats against his life and everything he thought he understood about his past.
Keywords: Trent, Will; (Fictitious character); Fiction; Atlanta; Fiction; Police; Georgia; Atlanta (Ga.); Fiction; Thrillers (Fiction); Detective and mystery fiction